2016
DOI: 10.1007/s00701-016-3041-8
|View full text |Cite
|
Sign up to set email alerts
|

The Fluoropen: a simple low-cost device to detect intraoperative fluorescein fluorescence in stereotactic needle biopsy of brain tumors

Abstract: The Fluoropen is a low-cost and simple standalone device for the detection of fluorescein fluorescence that can expedite stereotactic needle biopsy by providing instant confirmation of the diagnostic sample and therefore avoid the need for an intraoperative frozen section. In patients with non-contrast enhancing tumors and those who were pre-treated with dexamethasone prior to surgery, fluorescein fluorescence-guided stereotactic needle biopsy will need to be used with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Even in non-contrast-enhancing lesions, fluorescein harbors a specificity of 72%. Hence, our data correspond with previous studies that have also reported on usefulness of fluorescein in stereotactic biopsies by increasing the diagnostic yield and shortening operative time, although they mainly focused on contrast-enhancing lesions [ 11 , 14 , 19 ].…”
Section: Discussionsupporting
confidence: 91%
“…Even in non-contrast-enhancing lesions, fluorescein harbors a specificity of 72%. Hence, our data correspond with previous studies that have also reported on usefulness of fluorescein in stereotactic biopsies by increasing the diagnostic yield and shortening operative time, although they mainly focused on contrast-enhancing lesions [ 11 , 14 , 19 ].…”
Section: Discussionsupporting
confidence: 91%
“…[ 22 , 34 , 37 , 51 , 52 ] However, as aforementioned, its use has been reported only in 13 out of 57 studies on stereotactic biopsy in humans. [ 2 , 6 , 12 , 28 , 32 , 34 - 36 , 51 , 52 , 54 , 55 , 57 ] Furthermore, it increases the operative time and, consequently, the risk of complications. [ 35 ] Maybe even more importantly, the accuracy rate of this technique in the central nervous system lesions is only 77.9%, when compared to permanent section.…”
Section: Discussionmentioning
confidence: 99%
“…[ 52 ] However, on reviewing the literature over a period of 5 years (pubmed.com: June 2015/June 2020), only 13 out of the 59 original publications on stereotactic biopsy in humans[ 1 - 59 ] reported the use of frozen section. [ 2 , 6 , 12 , 28 , 32 , 34 - 36 , 51 , 52 , 54 , 55 , 57 ] In cases of cystic lesions, such as brain abscesses, the mere aspiration of pus is enough to confirm appropriate targeting, making pathology consultation unnecessary.…”
Section: Introductionmentioning
confidence: 99%
“…High-grade glioma tissue shows strong yellow fluorescence when excited at about 488 nm (47). Being a relatively inexpensive drug, fluorescein sodium could also be visualized using a low-cost miniature device, Fluoropen, which is essentially a LED torch with a blue filter mounted at the light source for excitation and a yellow filter attached around the torch as a cone collar (48). The device is positioned close to the specimen and yellow fluorescence is observed through the yellow filter (48).…”
Section: Methods For Biopsy Acquisition Guidance and For Rapid Intraomentioning
confidence: 99%
“…Being a relatively inexpensive drug, fluorescein sodium could also be visualized using a low-cost miniature device, Fluoropen, which is essentially a LED torch with a blue filter mounted at the light source for excitation and a yellow filter attached around the torch as a cone collar (48). The device is positioned close to the specimen and yellow fluorescence is observed through the yellow filter (48). Observation of fluorescein fluorescence from the specimens had a 100% positive predictive value and a 25% negative predictive value of a lesional tissue (49).…”
Section: Methods For Biopsy Acquisition Guidance and For Rapid Intraomentioning
confidence: 99%